Influence of Awe on Green Consumption: The Mediating Effect of Psychological Ownership - Wang, Liying; Zhang, Guangling; Shi, Pengfei; Lu, Xingming; Song, Fengsen (Frontiers in Psychology, 2019)
With the growing clamor for green development, in order to find an effective way and path of green development in the field of consumption, we take green consumption as a dependent variable, and consider the key antecedents, psychological mechanisms, and boundary conditions for effectively promoting green consumption. Green consumption is an ethical consumption mode based on self-sacrifice and a kind of decision-making based on ethical and moral limitations. Under the framework of emotion affect cognition theory, we assume that green consumption can be significantly promoted if it meets the needs of individual autonomous selection through positive emotional experience and awakens the consciousness that “the Earth is our homeland.” After investigating 589 subjects, the results showed that, compared with happiness and neutral emotions, awe can promote green consumption (H3) through psychological ownership (H2) as mediated by self-construal (H4). The role of psychological ownership between awe and green consumption is strengthened upon the activation of interdependent self-construal. However, the mediating effect of psychological ownership does not exist when independent self-construal is activated.